Football: A totality sport? Parallel history of German and Italian footballs in between two wars - Dietschy, Paul (Hispania Nova, 2019)
Totalitarian regimes have tried to use sport for political and ideological purposes and place it in a high position in their sports policies. First they wanted to put an end to the civil society of football by eliminating the existing federations or by appointing men loyal to their heads. Football was put at the service of the construction of the new man, who was not exempt from problems due to the professional and international culture of the game. Finally, totalitarian regimes sought to subvert internationalism in football, imposing their values and rituals or refusing to participate.
Keywords: Fascism; football; international relations; Stalinism; totalitarianism